2019
DOI: 10.3762/bjnano.10.142
|View full text |Cite
|
Sign up to set email alerts
|

Growth of lithium hydride thin films from solutions: Towards solution atomic layer deposition of lithiated films

Abstract: Lithiated thin films are necessary for the fabrication of novel solid-state batteries, including the electrodes and solid electrolytes. Physical vapour deposition and chemical vapour deposition can be used to deposit lithiated films. However, the issue of conformality on non-planar substrates with large surface area makes them impractical for nanobatteries the capacity of which scales with surface area. Atomic layer deposition (ALD) avoids these issues and is able to deposit conformal films on 3D substrates. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…We have also observed that many sALD reactions can be run even at room temperature, perhaps aided by the presence of the solvent. After demonstrating the sALD generation of oxides 32 and a cubic sulfide, 33 we have started expanding sALD beyond the confines of gALD materials families with a hydride 34 and a polymeric solid. 35 This study demonstrates the applicability of sALD to yet another interesting family of materials, namely transition metal dichalcogenides (TMDCs).…”
Section: Introductionmentioning
confidence: 99%
“…We have also observed that many sALD reactions can be run even at room temperature, perhaps aided by the presence of the solvent. After demonstrating the sALD generation of oxides 32 and a cubic sulfide, 33 we have started expanding sALD beyond the confines of gALD materials families with a hydride 34 and a polymeric solid. 35 This study demonstrates the applicability of sALD to yet another interesting family of materials, namely transition metal dichalcogenides (TMDCs).…”
Section: Introductionmentioning
confidence: 99%